UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG MELALUI PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER DENGAN PEMANFAATAN ALAT PERAGA SEDERHANA MATERI PEMBAGIAN SISWA KELAS II - Sumarni, Sumarni (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
The purpose of this study was to determine the effect of the application of cooperative learning modelNHT (Numbered Heads Together) against numeracy class divisions II SD Negeri 3 Mlekangacademic year 2014/2015. This research is a classroom action research with two cycles of stages ineach cycle; preparation of action plans, giving action, observation, reflection. The subjects were allstudents of class II. Before learning improvement of 8 students only two students who achievemastery learning, or 25%, while 6 students, or 75% has not been thoroughly studied. In the firstcycle of learning improvements, of 8 students there are 6 students who achieve mastery learning, or75%, whereas 2 students or 25% has not been thoroughly studied. Students' understanding of thematerial division two digit numbers from before repair than after the first cycle of learningimprovement has increased significantly. From 25% to 75%. From the results of evaluation of theindividual given before using learning model NHT (Numbered Heads Together) in the form of theuse of props simple, there are only 2 children of 8 students who already understand about thedivision number two figures, it means that only 25% of students who are capable and the rest asmany as six students, or 75% of students who have not been able. After the assessment of learningmedia in the form of the use of simple props, interests and learning outcomes of students increased to7 students (87.5%). While one student (12.5%) needs to enrichment and individual guidance, it isbecause the students do not attend or do not attend school during the discussion of the materialsupplied.